Analysis of Demand and Competition for Indonesia’s Eel in the International Market - Nurzakiah, Sitty; Nurmalina, Rita; Tinaprilla, Netti (Agro Bali : Agricultural Journal, 2025)
Indonesia is one of the main exporters of eels in the international market. Over the past few years, Indonesia has experienced a decrease in eel exports, despite a rise in world demand. This has triggered fierce competition between Indonesia and other exporting countries. This research aims to identify the demand and market competition for Indonesian eels in the international market. The analysis method used is the Almost Ideal Demand System (AIDS) Model. The data used is secondary data from Indonesia, China, Malaysia, the United States, India, Denmark, and the Netherlands in the last 11 years (2012 - 2023). The results of this research show that there is tight competition between Indonesia, China, India, and the United States in the international market. Meanwhile, the relationship between Indonesia’s frozen eels and frozen eels from Malaysia, Denmark, and the Netherlands tends not to compete in the international market. Frozen eel from Indonesia is a normal good, so when the price increases, it will cause a decrease in demand. Frozen eel from Indonesia is an inelastic commodity with the lowest elasticity value among other major exporters, so this can be an opportunity for Indonesia to determine the desired price. Overall, Indonesia is the third-largest exporting country that benefits the most when there is an increase in frozen eel export expenditure in the international market.